Pengaruh Store Atmosfer (Toko) pada Minat Beli Air Mineral Club - Mira Mira; Reichan Luiyyan Addani; Chandra Fitra Arifianto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
Packaged Drinking Water (PDW) has now become one of the most practical products dominating the market, offering a variety of advantages and benefits. The fierce competition among PDW producers drives consumers to be increasingly discerning and selective in making purchasing decisions. Consumer choices are often influenced by pressing needs, which have recently shifted toward a preference for more natural food and beverage products. However, amidst the fast-paced modern lifestyle, instant products remain a favored solution due to the convenience they offer. By leveraging store atmosphere strategies, this business has successfully stayed competitive and maintained its presence in the market. The relationship between store atmosphere and consumer purchase interest is significant, as first impressions often serve as a critical factor in consumer evaluations of a store. Elements such as exterior design, overall interior, store layout, and interior displays play a vital role in creating that appeal. This study aims to analyze the extent to which store atmosphere influences purchase interest in the Club brand bottled water. The research methodology involves distributing questionnaires to 100 respondents as the primary data source.